Human Capital and Productivity in the Sinaloa Commercial Family Businesses - Fabiola Ponce Durán; Marcel Rebeca Contreras Loera (International Journal of Small and Medium Enterprises and Business Sustainability, 2016)
Commercial family businesses are part of an open system that establish an ongoing relationship between the structure of the organization, objectives, people, environment and resources, adapting to changing needs which is required in the competitive environment. The paper shows results of the study that seeks to identify human factors that affect the level of productivity of family businesses in Sinaloa. It proposed a model that reflects relationships between these factors and productivity. Data collection was carried out with 209 respondents, and analyzed with a special constructed structural equation model. The results show that in a model of human factors that affect the level of productivity, behavior involves psychological and psychosocial processes that influence the performance of individuals and groups, increasing or decreasing the level of productivity of individuals, group of individuals and own organization. Three levels of analysis have been adopted that reflect the continuous interaction and mutual influence between each dimension. Based on the structural equation model, the paper concludes that among the three factors, individual factors have the highest correlation.